Simultaneous Caffeine Extraction and Enzymatic Inactivation through Microwave Thermobiochemical Process - Yulianto, Mohamad Endy; Madina, Haura Salwa; Aprilani, Berliana (Newinera Publisher, 2025)
Indonesia is known as one of the countries producing tea with high bioactive compounds such as caffeine, phenol, and catechin. This study evaluated the effectiveness of microwave-based thermobiochemical methods to extract the three compounds while simultaneously inactivating enzymes. The extraction process was designed using the Factorial Design method, involving variations in the feed:solvent ratio (1:22 and 1:32), temperature (110 °C and 130 °C), and time (10, 20, and 30 minutes). The results showed that catechin had the highest effect of 5.85 with a probability of 35.87%, followed by phenol (5.18; 59.68%) and caffeine (4.51; 54.47%). The normal probability plot graph indicated a distribution of effects approaching normal with R² of 0.9458 (catechin), 0.9395 (phenol), and 0.7946 (caffeine), respectively. Meanwhile, the optimization graph shows a perfect linear relationship (R² = 1), with optimal levels of 17.18 mg/L (catechin), 9.36 mg/L (phenol), and 9.77 mg/L (caffeine), respectively. Thus, this method is proven to be efficient and has the potential to be further developed for sustainable natural material processing industry applications. The variables were designed using the Factorial Design method.